Development and Validation of the Persian Version of the Acceptable Noise Level (ANL) Test in Normal Children Aged 5-8 Years - Abdollah Moossavi; Najmeh Shokoufeh; Saeideh Mehrkian; Akbar Biglarian; Younes Lotfi (Shiraz University of Medical Sciences, 2016)
Background: The goal of the present study was to develop and validate the Persian version of the Acceptable Noise Level (ANL) test in normal, Persianspeaking children aged 5-8 years. Methods: This tool-making and non-experimental research was conducted in two stages. In the first stage the proper story was selected and recorded after evaluation of its content validity. In the second stage this test material was administered to a total 181 normal children (97 girls and 84 boys) randomly chosen from the population of preschool and primary school children of Tehran (District 5), aged 5-8 years in four age groups to evaluate the reliability of test in order to develop the Persian version of the ANL test and assess its changes during the growth. Lawshe's method and Cronbach's alpha coefficient were used to assess the content validity and reliability of the test, respectively. Mann- Whitney U test was used to examine gender differences, and Kruskal-Wallis test was to examine age differences. Results: Test-retest correlation of 0.74 indicated acceptable reliability of the test. Significant differences were found between most of different age groups for the ANL mean scores (P<0.05). There was no significant gender difference for the ANL mean scores (P>0.05). Conclusion: The study results indicated good validity and reliability of the Persian version of the ANL test in children. Therefore this test can be useful in designing classrooms suitable for 5-8 year-old children of both genders.